IDENTIFIKASI MISKONSEPSI SISWA DALAM MENYELESAIKAN SOAL CERITA MATERI BILANGAN PECAHAN MENGGUNAKAN CERTAINTY OF RESPONSE INDEX (CRI) - Setyowati, Henny; Trapsilasiwi, Dinawati; Fatahillah, Arif (Kadikma, 2017)
Abstract. This research aims to describe: (1) seventh grade junior high school 1 Jelbuk students’ location of the misconception in solving word problem which involving fractions using Certainty of Response Index (CRI), (2) factors that cause seventh grade junior high school 1 Jelbuk students’ misconception in solving word problem which involving fractions. This research is descriptive research with qualitative approach. Data collection methods which were used are test and interview. As data collection tool instrument was used in form of 2 essay questions which acompanied with CRI scale. CRI scale between 0-5, if the low-confidence scale (CRI 0-2), then illustrates that the process of plowing plays a significant role in determining the answer. If the high-confidence scale (CRI 3-5), then describes the students have a high degree of certainty in using the knowledge they have to arrive at the answer. Research’s subject were students of VII B in Junior High School 1 Jelbuk which consists of 36 students. The results showed that on the number 1 problem there are 18 students experiencing misconception and 18 students do not experience misconception, whereas in problem number 2 there are 20 students experiencing misconception and 16 students do not experience misconception. Misconceptions experienced by students are in understanding the symbols, the area of ​​the rectangle, the operation of fractional numbers, the addition operation and the reduction of integers, the operation of the sum of the denominations and the operation of multiplication and division of integers. From the data obtained the most misconception experienced by students is misconception in understanding the symbol on the problem number 1 and misconception on the multiplication operation and the division of integers in question number 2. Keywords: Misconception, certainty of response index (CRI), fractions